ÁRVORES FRUTÍFERAS FUNCIONAIS DA FLORESTA ATLÂNTICA: DIVERSIDADE FENOTÍPICA E MOLECULAR, COMPOSIÇÃO HORMONAL, NUTRICIONAL E ANTIOXIDANTE EM Lecythis pisonis E Lecythis lanceolata - Araujo, Caroline Palacio de (2020)
The species Lecythis pisonis Cambess. and Lecythis lanceolata Poir. (Lecythidaceae), are chestnut trees native to the Atlantic Forest, whose seeds are food sources for fauna and humans. To study the biometric, hormonal and chemical characteristics of seed